How FOMO and Price Affect Online Purchase of Imitation Products - Rahmawati, Dwi Maya; Ambarwati, Rita; Turekulova , Dametken Medihanovna (Bina Nusantara University, 2025)
This research examined how factors such as Fear of Missing Out (FOMO), imitation of products, and price value influence consumers' impulsive buying and purchase intentions regarding imitation products online. A quantitative descriptive method was applied with data collected through surveys by distributing questionnaires. The sample was selected using a non-probability sampling technique with criteria: 1) residing in Indonesia, 2) aged 17 years or older, 3) having previously purchased imitation products online, and 4) willing to complete the entire questionnaire. A total of 207 respondents were analyzed. Data were processed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The findings suggest that FOMO and imitation products significantly impact online impulsive buying. Additionally, price value and online impulsive buying influence purchase intentions. There is also an indirect effect of FOMO and imitation products on purchase intentions through online impulsive buying. The research fills a gap in prior research that has rarely examined these variables' direct and indirect effects on online impulsive buying and purchase intention for imitation products. Theoretically, this research contributes to digital consumer behavior studies in the post-COVID-19 era, providing companies with a better understanding of factors influencing purchase intentions for imitation products.